DIVERSITAS KUPU-KUPU (RHOPALOCERA) DI DUSUN KUMU BARU KECAMATAN RAMBAH HILIRKABUPATEN ROKAN HULU RIAU - Putri, Elisa; Yolanda, Rofiza; Mubarrak, Jismi (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about the diversity of butterflies (Rhopalocera) in Dusun Kumu Baru Rambah Hilir district Rokan Hulu regency was conducted in November to January 2015 by using survey method. Samples were collected by using insect net and cylindrical gauze with 6 repetitions with random sampling techniques. Results showed, several butterfly was found with 7 families, 16 genera and 21 species. Diversity index value ranged from 1.04 to 2.81 and concluded in moderate category.